BUILDING STUDENT ENGAGEMENT IN TEACHING AND LEARNING: AREAS FOR ENHANCEMENT - Krouglov, Alex (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The paper analyses the engagement of students and teachers in developing a community of practice and the role of the institution in the process. Our research is based on surveys of students and teachers conducted in 2016 as part of the EU-funded Erasmus+ research project Internationalisation and Modernisation of Education and Processes in the Higher Education of Uzbekistan (IMEP). The questionnaires, developed by the project team of researchers, aimed to identify the areas of successful student engagement and where students did not engage actively in teaching, learning and other university and extracurricular activities. Our surveys of students and teachers provided us with the necessary information in order to establish the reasons for successful and less pro-active engagement of students. The results of the surveys also showed some differences in the level of engagement of teachers and students in the process of teaching and learning and how both groups viewed their involvement and the role of the institution. Two case studies presented by students selected for this project showcase their positive experience and confirm the results of our study. While the article deals with concrete data collected and analysed as part of the research, it addresses wider issues of student engagement, the provision of feedback and analyses the role of the main players in the process of teaching and learning enhancement.